Study of Implementation of Competency-Based BK at Pondok Pesantren Kiyai Haji Abdul Satar Sholeh - Widyarto, Wikan Galuh (Program Studi Bimbingan dan Konseling Islam, 2023)
The purpose of this study was to determine the form and effectiveness of a competency-based BK implementation study at the Kiyai Haji Abdul Satar Sholeh Islamic Boarding School. The type of research used in the thesis is qualitative research with a qualitative descriptive approach. The results of this study are, that the form of group guidance services carried out by counseling teachers is to carry out planning starting from identifying problems, conducting a need assessment (needs analysis), preparing RPL, facilities and infrastructure needed. As for the steps in implementing group guidance services, namely the initial or opening stage, the counseling teacher conductsgreetings and prayers, checks the presence of members, continues with introductions and conveys goals, activity phase, at this stage the counseling teacher determines the topic of discussion and delivery of material, discussion regarding the problem, conducting problem analysis and the Closing Stage, at this stage the counseling teacher concludes the meaning of the activity, conveys messages and impressions, plans follow-up, prays and greetings.